Cost reduction and productivity improvement through HRIS. (20th February 2020) - Begum, Halima; Bhuiyan, Faruk; Alam, A.S.A. Ferdous; Awang, Abd Hair; Masud, Muhammad Mehedi; Akhtar, Rulia
Employee productivity improvement and HR cost reduction are two useful options for a cost leader. This study aims to examine the association between human resource information systems (HRIS), employee productivity, and HR costs by focusing on the data of 40 Bangladeshi banks. The impact of one standard deviation variation of HRIS application on employee productivity and HR costs is then calculated using multiple regression analysis. The multivariate analysis of covariance (MANCOVA) is then tested to examine the variation of employee productivity and HR costs according to bank ownership patterns. Results indicate that the use of HRIS applications generated a higher efficiency in terms of employee productivity and the reduction of HR costs (where all things remain constant). It was also observed that employee productivity does not vary according to bank ownership patterns though stateowned banks and private-owned banks experience different HR costs.